2019
DOI: 10.21608/jesp.2019.68134
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Chitosan Nanoparticles Loaded With Albendazole on Parenteral Phase of Experimental Trichinellosis

Abstract: Most of the drugs used for trichinellosis treatment showed a limited bioavailability, a high degree of resistance and a weak activity against encapsulated larvae. Therefore, there is an urgent need to develop new agents to improve the bioavailability of these drugs. So, the aim of the present study was to assess the use of chitosan (CH) nanoparticles alone or loaded with full and half dose albendazole (ABZ) to increase albendazole dissolution rate, to enhance its antiparasitic activity during the muscular phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
5
9
0
Order By: Relevance
“…Likewise, Attia et al (2015) and Eid et al (2020) stated that muscles from ALB-treated mice showed massive inflammatory infiltration. Similarly, Nassef et al (2019) reported that ALB-treated mice showed inflammatory cellular infiltrate surrounding the larvae, which is consistent with the findings of Salama et al (2022) . In contrast, the muscle sections from mice treated with ALB and prednisolone showed mild to moderate inflammatory infiltration around larvae.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Likewise, Attia et al (2015) and Eid et al (2020) stated that muscles from ALB-treated mice showed massive inflammatory infiltration. Similarly, Nassef et al (2019) reported that ALB-treated mice showed inflammatory cellular infiltrate surrounding the larvae, which is consistent with the findings of Salama et al (2022) . In contrast, the muscle sections from mice treated with ALB and prednisolone showed mild to moderate inflammatory infiltration around larvae.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have investigated the efficacy of albendazole treatment. Reduction percentages in the number of T. spiralis larvae ranged from 28% to 98% ( Bany et al, 1992 ; Lopez-Garcia et al, 1997 ; Nassef et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Humans are infected through the consumption of raw or undercooked meat containing infective larva. Although this event occurs accidentally, the global prevalence of trichinosis is estimated to be around 11 million in humans [ 1 ]. Trichinella spiralis is the most virulent and pathogenic species to humans and has two lifecycle phases: an intestinal phase and a muscular phase [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this event occurs accidentally, the global prevalence of trichinosis is estimated to be around 11 million in humans [ 1 ]. Trichinella spiralis is the most virulent and pathogenic species to humans and has two lifecycle phases: an intestinal phase and a muscular phase [ 1 ]. In the enteral phase, muscle tissues are digested in the stomach, and larvae are released; larvae penetrate the intestinal mucosa of the small intestine and reach the adult stage within 48 h post-infection (p.i.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation